THE INFLUENCE OF LANDFORM IN THE DISTRIBUTION OF HOUSEHOLDS OF ILVA MICĂ TERRITORIAL ADMINISTRATIVE UNIT - ROȘIAN, Gheorghe; HORVATH, Csaba; MUNTEAN, Liviu; BACIU, Nicolae (Studia Universitatis Babeș-Bolyai Ambientum, 2021)
In the case of territorial administrative units located in hilly and mountainous lands, landform, through its morphometric parameters, is a variable that introduces significant differences in the distribution of households. A similar situation is the case of the Ilva Mică commune, where, due to its position at the border between the Eastern Carpathians and the Transylvanian Basin, the landform is extremely varied. Among the parameters of the landform taken into consideration for tracking the distribution of households, the following parameters stand out: altitude, slope and slope aspect. The results show that as the development of Ilva Mică took place, favorable lands were used for building households along with less favorable areas located at altitudes higher than the average altitude of the commune (704 m) and with slopes higher than 17°. This occurred both because of lack of space and of economic reasons, such as the land use for livestock.